2016
DOI: 10.3390/f7100216
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in Tree Diversity and Forest Structure of Evergreen Broadleaf Forests in Southern China along an Altitudinal Gradient

Abstract: Abstract:We studied the influence of altitude on the spatial heterogeneity of tree diversity and forest structure in a subtropical evergreen broadleaf forest in southern China. Significant positive correlation was found between tree species diversity, basal area and altitude, but negative correlation between slenderness of trunks and altitude. According to topography, tree species diversity, diameter at breast height, height and basal area increased from ridges to valleys, while slenderness and stem density di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
(61 reference statements)
3
8
0
Order By: Relevance
“…agreement with this study,Cui and Zheng (2016) also reported Shannon diversity index increased with altitude, with the highest diversity being recorded in the highest altitude in evergreen broadleaf forests in southern China. Zhang et al (2013) found the highest species diversity appeared in the middle elevation and under medium disturbance intensity in the Baihua Mountain Reserve, Beijing, China.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…agreement with this study,Cui and Zheng (2016) also reported Shannon diversity index increased with altitude, with the highest diversity being recorded in the highest altitude in evergreen broadleaf forests in southern China. Zhang et al (2013) found the highest species diversity appeared in the middle elevation and under medium disturbance intensity in the Baihua Mountain Reserve, Beijing, China.…”
supporting
confidence: 92%
“…The present study revealed that altitude has a significant effect on species diversity and richness. Altitude is a key variable affecting species diversity in mountains, as observed in numerous studies (Rahbek, 2005;Fetene et al, 2006;Muhumuza and Byarugaba, 2009;Kebede et al, 2013;Cui and Zheng, 2016). Similarly, a study by Kebede et al (2013) reported that aspect, slope and altitudinal variation in Ethiopian landscapes has influenced the existence of varied vegetation types and floristic diversity.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…As seen in the results of this study, elevation was the main influential factor in RF models. This variable is a significant predictor affecting species diversity, as observed in previous studies [81,82]. Similarly, aspect, slope and altitudinal variation in Ethiopian landscapes have influenced the existence of varied vegetation types and diversity [83].…”
Section: Effect Of Biotic and Abiotic Factors On Biodiversity Indexmentioning
confidence: 52%